(untitled) (Journal of Health, Technology and Science (JHTS), 2024)
Bleeding Time (BT) is a laboratory test to determine the length of time the body stops bleeding due to trauma made in a laboratory manner. This test measures hemostasis and coagulation. The coagulation factor will be activated to form fibrin threads that make platelet plugs stable, therefore bleeding can be stopped. The purpose of this study was to see the comparison of the results of the bleeding time examination of the Duke method and the Ivy method. The method in this study uses a quantitative approach with a cross sectional approach. The sampling technique in this study used accidental sampling technique, assuming a total sample of 24 samples. Using univariate data analysis techniques processed through the IBM SPSS Statistic V25.0 program. The results showed that in the Duke method there were 23 respondents (95.8%) who were normal, there was only 1 respondent (4.2%) whose results were abnormal. While the results of research using the ivy method obtained the results of all 24 respondents (100%) showed normal results. Based on the Independent T Test, it can be seen that p-value = 0.000< (α) 0.05 shows that there is a significant difference between the results of bleeding time examination using the Duke method and the ivy method in preoperative patients.